G405(P) To evaluate and compare the efficacy of combined sucrose and non-nutritive sucking for analgesia in newborns undergoing minor painful procedure: A randomised controlled trial. (27th April 2016) - Thakkar, P; Arora, K; Goyal, K; Das, R
Abstract : Aim: Neonates frequently undergo minor painful procedures for which they are often not offered any analgesia. Sucrose and Non-nutritive sucking (NNS) can be effective non-pharmacological methods for pain relief in neonates. Aim of the study was to evaluate and compare the efficacy of combined sucrose and non-nutritive sucking for analgesia in newborn infants undergoing minor painful procedure. Methods: This randomised control trial (RCT) was conducted in the neonatal intensive care unit of a tertiary care hospital over a period of one year. 180 full term neonates with birth-weight >2200 g and age >24 h were randomised to one of four interventions administered two min before the procedure: 2 ml of 30% sucrose (group I, n = 45) or non-nutritive sucking (NNS) (group II, n = 45) or both (group III, n = 45) or none (group IV, n = 45). Primary outcome was composite score based on Premature Infant Pain Profile (PIPP) score. Results: Baseline variables were comparable among the groups. Mean (±SD) PIPP score was 3.42 ± 1.6 in group III, 7.47 ± 1.6 in group I, 8.42 ± 2.5 in group II, and 12.49 ± 2.9 in group IV. Group III had significant decrease in the mean PIPP score compared to other groups (p = 0.001). Mean PIPP score also decreased significantly with any intervention as compared to no intervention (p = 0.001). Conclusions: Sucrose and NNS in combination are effective in providing analgesia in full term neonates undergoing minor painful procedure, with the combined intervention being more effective than single intervention.